EXPERT SYSTEM OF ARDUINO MICROCONTROLLER-BASED CATTLE CAGE SAFETY DETECTION WITH INFRARED PROXIMITY SENSOR - Herni Setyaningsih; Andino Maseleno; Rulin Swastika (International Journal of Artificial Intelligence and Robotic Technology (IJAIRTec), 2021)
Scurity is a basic need of the community in the current era of progress that is used to secure valuables. Scurity system is a security that has a circumcision that has been processed in the sense that it has been systemized according to its application in society or in an environment that is in accordance with its field. Farmers in the community are currently still troubled by the rampant theft of livestock. The rampant theft is also one of the factors in developing a security system, both data theft and theft in the form of goods or even livestock. The data collection methods used are observation, documentation, interviews, and literature studies. Making an Artificial Intelligence security system for Arduino-based livestock pens can provide reliable livestock cage security, because theft will be immediately accessed before carrying out the action. The design of the tool with this security system can provide information to the owner of the livestock shed that there is a thief approaching so that it can be used to maintain the safety of the livestock shed from theft.